DEVELOPMENT OF ANDROID-BASED INTERACTIVE E-MODULES FOR PHYSICS LEARNING ON MECHANICAL WAVE MATERIAL - Zohri Ratna (Jurnal Inovasi Fisika dan Edukasi, 2025)
The development of digital technology drives transformation in the world of education, including in the use of mobile-based learning media. Physics learning, especially in mechanical wave material, often faces obstacles in terms of understanding concepts due to limited visualization media that support the learning process. This study was conducted to develop and test the feasibility of an Android-based interactive e-module as a physics learning media that can improve the effectiveness and quality of student learning in mechanical wave material. This study is a development research (Research and Development) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The subjects in this study consisted of material experts, media experts, physics teachers, and grade XI students at one of the state high schools in Indonesia. Data collection techniques were carried out through expert validation, user response questionnaires (teachers and students), and learning outcome tests before and after using the e-module. The data collected were analyzed using quantitative descriptive analysis techniques, including validity, practicality, and effectiveness. The results showed that the interactive e-module developed was declared very valid with an average validation score of 91.25%. Teacher and student responses showed a high level of practicality with an average percentage of 89.7%. The effectiveness test produced an N-gain value of 0.72 which is included in the high category, indicating that the use of e-modules can significantly improve student understanding. It can be concluded that the Android-based interactive e-module developed in this study is suitable for use as a learning medium for mechanical wave material, and provides a positive contribution to improving the quality of physics learning in the digital era.